Evaluation of the inhalation toxicity of arecoline benzoate aerosol in rats. Issue 8 (22nd February 2022) - Chu, Ming; Fu, Guofeng; Deng, Jingjing; Wang, Ruoxi; Fan, Qiming; Chen, Zuxin; Lu, Jin; Liu, Xin‐an
Abstract: Arecoline is a pharmacologically active alkaloid isolated from Areca catechu . There are no published data available regarding the inhalation toxicity of arecoline in animals. This study aimed to evaluate the inhalation toxicity of arecoline in vitro and in vivo. For this purpose, arecoline benzoate (ABA) salt was prepared to stabilize arecoline in an aerosol. The MTT assay determined the half‐maximal inhibitory concentration values of ABA and arecoline in A549 cell proliferation to be 832 and 412 μg/ml, respectively. The toxicity of acute and subacute inhalation in Sprague–Dawley rats was evaluated using the guidelines of the Organization for Economic Cooperation and Development. For acute inhalation, the median lethal concentration value of ABA solvent was >5175 mg/m 3 . After the exposure and during the recovery period, no treatment‐related clinical signs were observed. In the 28‐Day inhalation toxicity test, daily nose‐only exposure to 2510 mg/m 3 aerosol of the ABA solvent contained 75 mg/m 3 ABA for male rats and 375 mg/m 3 ABA for female rats, which caused no observed adverse effects, except for the decreased body weight gain in male rats exposed to 375 mg/m 3 ABA. In this study, the no observed adverse effect level (NOAEL) for the 28‐day repeated dose inhalation of ABA aerosol was calculated to be around 13 mg/kg/day for male rats and 68.8 mg/kg/day for female rats, respectively. Abstract : The aim of this study was to evaluate the inhalation toxicity of arecoline in vitro and in vivo. Arecoline benzoate (ABA) salt was prepared to stabilize arecoline in an aerosol. The LC50 value of ABA solvent was >5175 mg/m 3 for acute inhalation. No clinical signs were observed after exposure. The no observed adverse effect level (NOAEL) for 28‐day repeated dose inhalation of ABA aerosol was 13 mg/kg/day for male rats and 68.8 mg/kg/day for female rats respectively.